Between monotheism and tawhid: a comparative analysis - Hashi, Abdurezak Abdulahi (Revelation and Science, IIUM, 2013)
In the contemporary academic domains, there are incidents where ‘monotheism’ and ‘tawhid’ are employed as synonymous terms; as if these concepts signify the same conceptual denotations about the belief and the unity of God; and as a result, religious faiths like Judaism, Christianity and Islam, are categorized as monotheists. However, is it true that monotheism and tawhid are synonymous or identical concepts? Through analytical and comparative methods, this paper aims to compare and contrast between these two concepts, and identify the true conceptual and theological properties of each term.